Influence of Deep Tillage and Liming on Soil Quality: Physical Attributes, Microbial Activity, and Sugarcane Yield in Clay Soils - Pacola, Marcela [UNESP]; Guimarães, Tiara Moraes; Calonego, Juliano Carlos [UNESP]; de Araújo, Fábio Fernando; Rigon, João Paulo Gonsiorkiewicz; Bossolani, João William [UNESP]; Jacomassi, Lucas Moraes [UNESP]; Viveiros, Josiane [UNESP]; de Siqueira, Gabriela Ferraz [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Springer Nature, 2025)
Soil degradation is a major challenge for sugarcane production in tropical regions. This study evaluated the effects of deep tillage combined with localized liming on soil quality, microbial activity, and sugarcane productivity in a clay Hapludox. A randomized block design with four replicates and a 4 × 2 factorial scheme comprising four treatments: conventional tillage without liming (CT0), conventional tillage with liming (CT2), deep strip tillage without liming (DT0), and deep strip tillage with liming (DT2) in 2 years of evaluation (2017—1st ratoon; 2019—3rd ratoon). Soil attributes evaluated were macroporosity, aggregate stability, soil organic carbon (SOC), microbial biomass (Cmic), enzyme activity and Stalk and sugar yields were also assessed. The results demonstrated that DT2 significantly improved soil fertility, alleviated compaction, and increased aggregate stability. In 2019, Ca2⁺ and Mg2⁺ contents in DT2 were 30.5 mmolc dm⁻3 and 25.0 mmolc dm⁻3, respectively, more than twice those in CT0. DT2 also showed the highest soil respiration (RESP) and metabolic quotient (qCO₂), associated with elevated microbial activity. Liming increased stalk and sugar yields by 15% and 28%, respectively, in 2017. Redundancy analysis revealed that pH (F = 15.60) and Ca2⁺ (F = 7.19) were key contributors to improved productivity.These findings suggest that deep tillage with localized liming is an effective strategy to enhance soil quality and crop yield while promoting sustainable sugarcane cultivation.